Prenatal Diagnosis of Fetal Visceral Situs Abnormalities: A Retrospective Study - Xiaoping Gong; Mingli Lv; Guanjie Wang; Yunyun Cao; Ping Chen; Hui Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: To explore the necessity for prenatal diagnosis and evaluate related diagnostic methods for fetal visceral situs abnormalities. Methods: A retrospective analysis was performed to examine the clinical data and pregnancy outcomes of 43 cases of fetal visceral situs abnormalities diagnosed at our hospital between May 2018 and September 2023, using prenatal ultrasound consultation as the diagnostic standard. Results: Among the 43 cases of fetal visceral situs abnormalities, 46.51% (20/43) were diagnosed as situs inversus, of which 95.00% (19/20) had no associated cardiac structural abnormalities. Heterotaxy syndrome accounted for 53.49% (23/43) of cases and was associated with cardiac structural abnormalities (100.00%, 23/23) of these patients. The most common cardiac abnormalities involved a single atrium and a single ventricle (56.52%, 13/23), followed by double-outlet right ventricle (34.78%, 8/23), and pulmonary artery stenosis (30.43%, 7/23). Amniocentesis was performed in 21 (48.84%, 21/43) cases, with both chromosomal karyotyping and chromosomal microarray analyses yielding negative results. Among these cases, 15 underwent whole-exome sequencing (WES), which identified 5 with suspected pathogenic gene variants related to primary ciliary dyskinesia (PCD) and 1 with Holt–Oram syndrome (HOS). Conclusions: Prenatal ultrasonography is a reliable method for diagnosing fetal visceral situs abnormalities. Moreover, for fetuses diagnosed with visceral situs abnormalities and pregnant women with normal chromosomal results, WES remains essential to improve the detection rates of PCD or other genetic abnormalities.